Comparison of polymethoxyethylacrylate-coated circuits with leukocyte filtration and reduced heparinization protocol on heparin-bonded circuits in different risk cohorts - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2006)
Objectives: The relative benefits of strategic leukofiltration on polymer-coated and low-dose heparin protocol on heparin-coated circuits were studied across EuroSCORE patient risk strata for three different cohorts. Methods: In a prospective, randomized study, 270 patients undergoing coronary artery bypass grafting were allocated into three groups (n = 90): Group 1 - polymethoxyethylacrylate-coated circuits + leukocyte filters; Group 2 - polypeptide-based heparin-bonded circuits with reduced heparinization; and Group 3 - Control: uncoated circuits. Each group was further divided into three subgroups (n = 30), with respect to low- (EuroSCORE 0-2), medium- (3-5), and high- (6+) risk patients. Blood samples were collected at T1: following induction of anesthesia; T2: following heparin administration; T3: 15 min after CPB; T4: before cessation of CPB; T5: 15 min after protamine reversal; and T6: ICU. Results: In high-risk cohorts, leukocyte counts demonstrated significant differences at T4 and T5 in Group 1, and at T4 in Group 2. Platelet counts were preserved significantly better at T4 and T5 in both groups (p < 0.05 versus control). Serum IL-2 and C3a levels were significantly lower at T3, T4 and T5 in Group 1, and T4 and T5 in Group 2 (p < 0.05). Postoperative bleeding, respiratory support time and incidence of atrial fibrillation were lower in the study groups versus control. Cell counts on filter mesh and heparin-coated fibers/ circuits were significantly higher in the high-risk cohorts versus uncoated fibers. Phagocytic capacity increased on filter mesh, especially in high-risk specimens. SEM evaluation demonstrated better preserved coated circuits. Conclusion: Leukofiltration and coating reduced platelet adhesion, protein adsorption, atrial fibrillation and reduced heparinization acted via modulation of systemic inflammatory response in high-risk groups.
Keywords: CARDIOPULMONARY BYPASS EQUIPMENT; EXTRACORPOREAL CIRCUITS; RANDOMIZED-TRIAL; CARDIAC-SURGERY; DURAFLO-II; IN-VIVO; BIOCOMPATIBILITY; ANTICOAGULATION; REPERFUSION; COMPLEMENT